Let Rhoda Speak Again: Identity, Uncertainty, and Authority in Virginia Woolf’s The Waves - Myk, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2011)
Performing a rereading of Virginia Woolf's 1931 experimental modernist masterpiece of The Waves, in this article I focus on the elusive and conflicted character of Rhoda, whose significance has been either overlooked or marginalized in the available criticism of the narrative. By pointing out a number of problems in the existing scholarship devoted to Rhoda, I propose to define her as a transgressive figure of uncertainty through which Woolf develops a critique of the unitary self. My point of departure for the following essay is Toril Moi's perspective on Woolf's oeuvre as openly feminist and deconstructive. Consequently, I begin with Moi's emphasis on Woolf's commitment to the problematization of the Western male humanism's underlying concept of the unitary self. Drawing from a number of critical and philosophical perspectives, I turn to Kim L. Worthington's idea of subjectivity as a sustained process of interpersonal narrativization in order to offer a more nuanced account of Rhoda's identity as compound and implicated in the dynamics of inter-subjective processes. I also consider Rhoda's much criticized rejection of identity vis-à-vis Woolf's strategy of impersonality, and, contrasting it with Maurice Merleau-Ponty's phenomenological concepts of the flesh and anonymous existence, I contend that Rhoda renounces the unitary selfhood, which corroborates Moi's critique of Woolf. Through a close analysis of Rhoda's position versus the other characters, as well as by examining how Rhoda's ego boundaries are delineated in the narrative, I demonstrate that Woolf's conflicted heroine emerges as an astute critic of gendered reality, since she is the one who most acutely feels the dualistic nature of selfhood and it is chiefly through her that Woolf points to the need to overcome this dualism. Shannon Sullivan's feminist revision of the Merleau-Pontian perspective on the anonymity and the body as well as the Deweyan notion of transactionality further helps to elucidate the ways in which Rhoda's experimental and subversive discourse engages in a polemic with the Cartesian conceptualization of identity presupposed on the dualism of mind and body simultaneously inquiring about a possibility of a non-dualistic and non-unitary conception of subjectivity. As a consequence, Rhoda gains authority and agency through uncertainty which prompts her to adopt an uncompromisingly and insistently questioning stance. Finally, I suggest reconsidering Rhoda's suicide as a metaphorical act of ‘distancing,’ as discussed by Zygmunt Bauman, via Adorno, in his 2006 Liquid Fear, another context for approaching Rhoda's uncertainty.